Jellyfish Sting: Sebuah studi Kasus Indonesia [Jellyfish Sting : An Indonesian Case Report] - Nova Mujiono (Faculty of Fisheries and Marine Universitas Airlangga, 2010)
AbstractJellyfish sting cases are reported between the years 2005 to 2009 from Indonesian waters. Three fatal cases occurred in Jebus and Situbondo in 2008 which predicted to be caused by Chrysaora quinquecirrha and Physalia physalis. Another species, Physalia utriculus is causing no fatality. Seasonality, treatment of the injury and prevention from the sting also discussed.